An analysys of muscle balance in professional field hockey players - Kawalek, K.; Garsztka, T. (Trends in Sport Sciences, 2013)
Introduction. The purpose of practicing sport is to improve one`s physical fi tness and technical skills. Highly specialized training strengthens particular muscles, which due to repeated overuse may become hypertonic and shortened. This kind of disorder of soft tissues surrounding joints limits the articular range of motion and causes pain, which in effect reduces an athlete`s ability to compete. Aim of Study. The aim of this study was to evaluate the state of muscle balance in fi eld hockey players. The research sample consisted of seventeen professional players from the Polish National Field Hockey Team from 2009. Material and Methods. The research methods included muscle length tests and a questionnaire survey on players` pain symptoms and their knowledge about maintaining muscle balance. Results. Insignifi cant asymmetric muscle balance disorders were found in the upper limb region. The external rotators of the shoulder joint were the most overused muscles. Signifi cant symmetric muscle length disorders were found in the lower limb region - the iliopsoas was shortened in 100% of cases, and rectus femoris in 63 %. Conclusions. Several conclusions were drawn. The most significant one is that all fi eld hockey players exhibit disturbances in muscle length and suffer pain. This research shows which muscles are highly overloaded and should be taken into consideration in developing programs of stretching exercises. To improve the effi ciency of these exercises they should be s pervised by an experienced physiotherapist.